PERAN EFEK IMUNOMODULASI VITAMIN D PADA TATALAKSANA COVID-19 - Kadek Anggiswari Pradnya Angela; I Nyoman Sutarka (Faculty of Medicine Universitas Mataram, 2022)
COVID-19 infection is marked by SARS-CoV-2 binds with ACE-2 receptors. In this process, the virus will avoid immunity systems, followed by a cytokine storm in some patients. Aside from calcium homeostasis and bone metabolism role, vitamin D plays role in reducing inflammation process and immunoregulation, which is known as the immunomodulation effect. Vitamin D plays a role against pathogens in adaptive and innate immune systems. Vitamin D modulates T-helper (Th) cells response inducing response shift from Th1 to Th2, increasing T-regulatory (Treg) cells development, and balancing T-helper cells response against pathogens and reducing pro-inflammatory cytokines production. Vitamin D may reduce production of pro-inflammatory cytokines such as TNF-?, IL-6, IL-1?, IL-12, and IFN-?, caused by inhibition of nuclear factor kB (NF-kB) activation. Vitamin D also induces ACE-2 vasorelaxant converting Angiotensin II into Angiotensin VII, a vasodilator, to prevent Acute Respiratory Distress Syndrome (ARDS) from happening. Few studies show COVID-19 patients has vitamin D deficiency. A meta-analysis study of 360,972 COVID-19 patients shows 37.7% of them with vitamin D deficiency and 32.2% with vitamin D insufficiency. Vitamin D deficiency correlates with COVID-19 severity and mortality. A study of 42 patients with acute respiratory failure caused by COVID-19 in Bari, Italy shows patients with vitamin D levels < 10 ng/ml have 50% mortality rate after 10-days of care. Vitamin D level examination is recommended for COVID-19 patients. The recommendation for vitamin D supplementation is vitamin D3 4000 IU/day dose for 7 days continued with 800-1000 IU/day maintenance dose for vitamin D deficiency patients.